New Strait Times, 21 Disember 2010 - Lim Chia Ying (The New Straits Times Press (M) Bhd, 2010)
The Mass Rapid Transit (MRT), seen as a system that will operate at higher speeds and carry more passengers than the exixting Light Rail Transit (LRT), has generated much interest of hoe it will boost Klang Valley's public transportation.